PEMAHAMAN JAMA’AH TABLIGH TENTANG UMMAT TERBAIK DALAM AL- QUR’AN SURAH ALI-IMRAN AYAT 110 - Achmad Ghozali Syafi'i; Sawaluddin Siregar; Dahliati Simanjuntak (Amsal Al-Qur’an: Jurnal Al-Qur’an dan Hadis, 2025)
This study focuses on the understanding of the Tabligh congregation regarding the Qur'an Surah Ali Imran verse 110, which states that the best Muslims are those who carry out Allah's commands, preach, and invite to goodness and prevent evil. The method used in this study is a qualitative method with a field approach. Data were collected through in-depth interviews with several members of the Tabligh congregation, observations of the Tabligh congregation's preaching activities, and analysis of documents or literature used in the preaching process. The results of the study show that the Tabligh congregation understands the "best ummatan" as a community that always tries to practice Islamic law purely, with a focus on preaching, worship, and a simple life that distances itself from worldly luxuries. The Tabligh congregation considers that the best community is the Tabligh congregation that has a high commitment to religious teachings and tries to invite other people to follow these teachings through real actions. Preaching is one of the main manifestations of the understanding of the "best ummatan". This concept influences the lifestyle of the Tabligh congregation which is more focused on devotion to Allah and continuous self-development. social life and preaching.